Prevalence and antimicrobial-resistant Campylobacter jejuni and Campylobacter coli in free-range chickens in northwest Ethiopia - Worku, M.; Tessema, B.; Ferede, G.; Ochieng, Linnet; Leliso, S.A.; Mutua, Florence; Moodley, Arshnee; Gelaw, B.; Grace, Delia (American Society of Tropical Medicine and Hygiene, 2025)
Campylobacter enteritis is the most common bacterial foodborne disease in humans. Long-term use of antibiotics in chicken production may result in antimicrobial resistance in Campylobacter strains. Information on the antimicrobial resistance profile of Campylobacter species among free-range chickens in Ethiopia is scarce. Hence, this study aimed to determine the prevalence and antimicrobial resistance of Campylobacter jejuni and Campylobacter coli among free-range chickens in Amhara National Regional state, northwest Ethiopia from November 1, 2022 to April 30, 2023. Cloacal swabs were collected from free-range backyard chickens, directly inoculated onto modified charcoal cefoperazone deoxycholate agar, and incubated at reduced O2 concentration at 42°C for 48 hours. Suspected colonies were confirmed at the species level using matrix-assisted laser desorption ionization time-of-flight mass spectrometry. The associated factors were analyzed using the Fisher exact test. A P <0.05 at 95% CI was considered statistically significant. Among the 286 cloacal samples, 15.0% (n = 43/286; CI: 10.2–19.5) were positive for Campylobacter species. C. jejuni (60.5%) was more frequent than C. coli (39.5%). Of the total isolates, 62.8% (n = 27/43), 51.2% (n = 22/43), and 16.3% (n = 7/43) of the Campylobacter species were resistant to tetracycline, ciprofloxacin, and erythromycin, respectively. Of the total Campylobacter species isolates, 9.3% (n = 4/43) were multidrug resistant. Campylobacter species resistance to tetracycline and ciprofloxacin was high in general among backyard chickens. Multidrug-resistant Campylobacter species were also identified, and they require special attention to prevent the potential dissemination of the strains to humans in the community.